Design and application examples of CMOS fractional-order differentiators and integrators. (January 2019) - Bertsias, Panagiotis; Psychalinos, Costas; Elwakil, Ahmed; Safari, Leila; Minaei, Shahram
Abstract: Reduced complexity CMOS fractional-order differentiator and integrator building blocks are introduced in this work, based on 2 nd -order integer-order transfer function approximations. These blocks are then used for implementing fractional-order filters as well as a Leaky-Integrate-and-Fire Mihalas-Niebur neuron model. Cascading 1 st and 2 nd -order blocks to obtain 5 th -order integer-order transfer functions, improved bandwidth of approximation accuracy is achieved. Furthermore, the realization of fractional-order capacitor and inductor emulators is demonstrated.